2002
DOI: 10.1021/ma020394+
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Properties and Polymorphic Behavior of Fibers of Syndiotactic Polypropylene at Different Temperatures

Abstract: An analysis of the elastic properties of syndiotactic polypropylene at different temperatures is reported. Fibers stretched at low temperatures are in the trans-planar form III, which transforms into the helical form II upon the release of the tension, whereas fibers stretched at high temperatures are in the stable helical form I. The mechanical analysis of these fibers has shown that only at room temperatures the specimens show good elastic properties. The elastic recovery of the samples is in part lost also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
138
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(156 citation statements)
references
References 27 publications
18
138
0
Order By: Relevance
“…Syndiotactic polypropylene (s-PP) presents a very complex polymorphic behavior (the first part of this section on s-PP modifications is reported in the publication [203][204][205][206][207][208][209][210][211][212]). s-PP chains crystallize to various polymorphic crystalline phases and, depending on the degree of stereoregularity and the mechanical and thermal history, different degrees of statistical disorder are present in the crystal packing.…”
Section: Polymorphism Of Syndiotactic Polypropylenementioning
confidence: 99%
See 2 more Smart Citations
“…Syndiotactic polypropylene (s-PP) presents a very complex polymorphic behavior (the first part of this section on s-PP modifications is reported in the publication [203][204][205][206][207][208][209][210][211][212]). s-PP chains crystallize to various polymorphic crystalline phases and, depending on the degree of stereoregularity and the mechanical and thermal history, different degrees of statistical disorder are present in the crystal packing.…”
Section: Polymorphism Of Syndiotactic Polypropylenementioning
confidence: 99%
“…Form III is obtained by stretching at room temperature the compression-molded samples, as found by Natta et al It is characterized by chains in zigzag trans-planar conformation. Its crystal structure has been reported recently [203][204][205][206][207][208][209][210][211][212] and belongs to the space group P2 1cn . In this form, the trans-planar chains are packed in orthorhombic unit cells with axes a ¼ 5. , Cu Kα).…”
Section: Polymorphism Of Syndiotactic Polypropylenementioning
confidence: 99%
See 1 more Smart Citation
“…The improved sPP has high crystallinity and melting temperature and has outstanding physical properties. The important physical properties are high mechanical strength and high toughness in spite of the high crystallinity and relatively high glass transition temperature [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The importance lies on its excellent toughness and elastic properties. Previous investigations [1][2][3][4][5][6][7] indicated that sPP presents a complex polymorphic behavior, and four crystalline forms have been found so far. The most stable form I and the metastable form II are characterized by chains in s (2/1)2 helical (t 2 g 2 ) n conformation, packed in orthorhombic unit cells.…”
Section: Introductionmentioning
confidence: 99%